Fabricação e estudo de um secador solar de exposição direta de baixo custo - SILVA JÚNIOR, IVANALDO CORTEZ (2018)
Nowadays, in the face of constant increases in energy generation and distribution costs and aggression to the environment through fossil fuel derivatives, it is necessary to seek clean and renewable energy sources. Thus, solar energy presents itself as a viable alternative for solving these problems and social demands. Drying food using energy emanating from the sun is an activity developed by some societies since ancient times and still shows a fairly viable technique to increase the storage period of food. Thus, the objective of this work was to study a solar dryer of direct exposure in natural convection drying of mullet (Mugil brasiliensis). For this, it was planned, manufactured and tested in operation as a dryer, checking the thermal efficiency of the dryer and drying, as well as the economical viability of the entire process. The dryer was made of simple materials and easy access (plywood, zinc sheet and pieces of glass from reused windows). The work shows the collection of data related to the dehydration of the fish, as well as those referring to the transfer of thermal and mass energy in the dryer. From the information collected and correlating it with the contents of the tables of properties contained in the specialized literature of the thermal area, the losses and yields of the studied process were calculated. Satisfactory fish dewatering was achieved, despite the low thermal efficiency of the solar equipment. The low mass flux, characteristic of processes based on natural convection, was determinant in obtaining the reduced thermal yield of the dryer.